C–H oxidation enhancement on a gold nanoisland by atomic-undercoordination induced polarization. Issue 26 (26th May 2020) - Lin, Zezhou; Hirao, Hajime; Sun, Changqing; Zhang, Xi
Abstract : The valence band polarization of an under-coordinated corner atom enhances the electron-donation ability and enables the C–H oxidation of an Au nanoisland. Abstract : C–H activation is of great significance in the chemical industry while an effective solvent-free catalyst is highly desired. This work shows that a gold nanoisland which was inert in the bulk is effective for C–H activation reactions. We investigated the C–H activation of toluene on an Au nanoisland (58 atoms) using relativistic density functional theory (DFT). We found that (i) the bonds between under-coordinated gold atoms (corner site) shrink spontaneously and become stronger; (ii) the valence charges of corner atoms are polarized to the upper edge of the valence band (near the Fermi level), indicating the electron donation ability in the catalytic process; (iii) during C–H oxidation, the indirect path (O2 dissociation and O–H bonding) and direct path (O2 –H bonding) were considered. The Au–O2 complex is active enough to abstract a hydrogen atom directly from toluene, with a barrier that is 6.8 kcal mol −1 lower than that of the indirect path; and (iv) a transfer of up to ∼0.8 electrons from gold to O2 occurs. Moreover, hybridization between delocalized gold orbitals and oxygen p-orbitals leads to the stabilization of the singlet spin state of Au58 O. Our results suggest that undercoordination-charge-polarization are key factors for the C–H oxidation catalyzed by an Au nanoisland.